Egg-associated Salmonella enterica serovar Enteritidis: comparative genomics unveils phylogenetic links, virulence potential, and antimicrobial resistance traits - Abdelhamid, Ahmed G.; Yousef, Ahmed E. (Frontiers in Microbiology, 2023)
Salmonella enterica serovar Enteritidis (SE) remains a frequent cause of foodborne illnesses associated with the consumption of contaminated hen eggs. Such a food–pathogen association has been demonstrated epidemiologically, but the molecular basis for this association has not been explored. Comparative genomic analysis was implemented to decipher the phylogenomic characteristics, antimicrobial resistance, and virulence potential of eggs-associated SE. Analyzing 1,002 genomes belonging to 841 sequence types of food-isolated SE strains suggests a high genomic similarity within the egg-related lineage, which is phylogenetically close to SE strains isolated from poultry but is different from those isolated from beef. Core genome- and single nucleotide polymorphism (SNP)-based phylogeny of 74 SE strains of egg origin showcased two distinct sublineages. Time-scaled phylogeny supported the possibility of a common ancestor of egg-related SE lineages. Additionally, genome mining revealed frequent antibiotic resistance due to the presence of aac(6’)-Iaa and mdsAB encoded on the genomes of egg-associated SE strains. For virulence gene profiling, 103–113 virulence determinants were identified in the egg-associated SE, which were comparable to 112 determinants found in human-associated SE, emphasizing the capacity of egg-associated strains to infect humans and cause diseases. The findings of this study proved the genomic similarity of egg-associated SE strains, and these were closely related to poultry strains. The egg-associated strains also harbor virulence genes equivalent to those found in human-associated SE strains. The analysis provided critical insights into the genetic structure, phylogenomics, dynamics of virulence, and antibiotic resistance of Salmonella Enteritidis, circulating in eggs and emphasizing the necessity of implementing anti-Salmonella intervention strategies, starting at the production stage of the poultry supply chain.